DEVELOPING WEB-BASED READING LEARNING MATERIALS FOR GRADE VIII STUDENTS OF SMP NEGERI 8 MEDAN - Windi Abdillah; Nora Ronita Dewi; Juli Rachmadani Hasibuan (Universitas Negeri Medan, 2018)
This study aimed at identifying the needs of grade eight students of SMP Negeri 8 Medan in learning reading English using website and concerns on how web-based reading learning materials are developed for grade VIII students of junior high school. The nature of this study is Research and Development (R & D). The steps were conducting the needs analysis, writing the course grid, storyboarding, writing the first draft, obtaining the experts’ judgments, revising the first draft, and finally writing the final draft. This study involved 32 students of the eight grade students of SMP Negeri 8 Medan as the research subjects. The instruments for collecting the data were questionnaires (needs analysis questionnaire and expert judgment questionnaires). The results of the needs analysis questionnaire were analyzed using percentage and the expert judgment were analyzed using descriptive statistics. Data got from the result of need analysis was being the basis in developing the product. The website was divided into five pages: Home, Start Up, Your Focus, Your Activity, and Grammar Corner. Then, based on the expert judgment, the website are appropriate for the grade eight students of junior high school. It was proved by the mean value of 4.2 for web based materials which cover the appropriateness of content, language, and presentation, and 4.5 for the website.Key words: Research and Development (R&D), Website, Reading Materials, Junior High School